Prediction of environmental suitability for Haematoxylum campechianum: A proposal to promote reforestation in Mexico - Anay Serrano-Rodríguez; Annery Serrano Rodríguez; Yarelys Ferrer-Sánchez; Fernando Abasolo-Pacheco; Mariela Alexi Díaz Ponce; Norma María Guerrero Chuez; Pedro Harrys Lozano Mendoza; Alexis Herminio Plasencia-Vázquez (Global Ecology and Conservation)
Models of potential distribution and ecological niche allow to estimate priority areas for the management of species of interest, as well as to identify variables related to environmental suitability and predict the behavior of species in the face of anthropogenic disturbances. Logwood (Haematoxylum campechianum) is a species that we consider a natural heritage in southeastern Mexico because of its ecological role and the current and historical use of its wood. This species is present in different vegetation types and even dominates in some ecosystems called ''tintales'', which have been exploited for dye extraction in past centuries. This, combined with changes in land use for livestock, agriculture, and other anthropogenic activities, has affected the Logwood´s distribution and connectivity of its populations. We modeled the potential distribution of H. campechianum and evaluated the feasibility of reforestation with this species in southeastern Mexico. For this purpose, we included 638 occurrence points and used the MaxEnt algorithm for modeling, analyzing different parameters. We used the potential distribution model, accessibility to the areas and water availability to calculate a feasibility index for reforestation. The environmental suitability for the species is more present in southeastern Mexico, conditioned by the aridity index, the minimum temperature of the coldest month and the maximum temperature of the warmest month. The greatest percentage of areas with high feasibility indexes for reforestation are found in Campeche, apparently a key state for the conservation and management of the species. This study can be the starting point for implementing reforestation programs with H. campechianum and can be used as an example to apply to other species with patrimonial value.